2013
DOI: 10.1016/j.jcf.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stenotrophomonas maltophilia infection and mortality or lung transplantation in cystic fibrosis patients

Abstract: Baseline chronic S. maltophilia infection is associated with an almost three-fold increased risk of death or lung transplant in CF patients. It is still unclear, however, whether chronic S. maltophilia infection is simply a marker of severity of disease and ultimate mortality or whether it is causally related to disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 21 publications
4
87
4
Order By: Relevance
“…The registry has few patients LTFU and complete data on patient deaths, making this a robust resource for epidemiology studies. Our results showed a protective effect associated with S. maltophilia, which differs from a previous study by WATERS et al [23], who reported that chronic infection with S. maltophilia was associated with increased mortality or lung transplantation. The discrepancy in results may be due to our inability to differentiate between chronic and intermittent infection, which is a limitation of the data source.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The registry has few patients LTFU and complete data on patient deaths, making this a robust resource for epidemiology studies. Our results showed a protective effect associated with S. maltophilia, which differs from a previous study by WATERS et al [23], who reported that chronic infection with S. maltophilia was associated with increased mortality or lung transplantation. The discrepancy in results may be due to our inability to differentiate between chronic and intermittent infection, which is a limitation of the data source.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the prevalence of bacteria such as S. maltophilia and MRSA has increased while the prevalence of BCC is declining. These trends are important to recognise as these data have potential infection control implications and prior literature has shown that infection with these organisms can have a significant negative impact on survival [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Stenotrophomonas infections have been associated with poor prognosis for cystic fibrosis treatment. 52 We found that concurrent treatment with antibiotics and probiotics lead to an increase in microbial diversity, albeit a small percentage and not statistically significant. The probiotics themselves did not persist in the ceca or large intestine of antibiotic treated mice, but it did promote the presence of more Firmicutes and Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 60%
“…pulmonary exacerbation, and greater rates of mortality or need for lung transplantation (50)(51)(52)(53)(54)(55). P. aeruginosa, B. cepacia complex, and S. maltophilia are found in the environment and have consequently developed ways of surviving in harsh milieus with exposure to naturally occurring antimicrobials.…”
Section: Ats Seminarsmentioning
confidence: 99%